Adoção da modelagem matemática para professores em um contexto de formação continuada - Mutti, Gabriele de Sousa Lins (2020)
The term adoption of Modeling has been repeatedly mentioned in the literature produced in the context of Mathematics Education. Although it is recurrent, these mentions have been predominantly focused on the procedures, and discussions that seek to understand the meaning of adoption for the teacher are not explicit. Considering the absence of studies in this direction, attested by the literature review presented in this thesis, organized in the Multipaper format, we ask: what is this, adoption of Mathematical Modeling for teachers inserted in a context of continuing education? Guided by this question, assumed from the phenomenological perspective of research, we sought to interview 25 basic education teachers who participate in the Continuing Education of Teachers in Mathematical Modeling in Mathematical Education, in the municipalities of Cascavel, Francisco Beltrão, Foz do Iguaçu and Tupãssi, in the state of Paraná. The careful analysis of the text of the transcription of the interviews, optimized with the help of the Atlas ti software, allowed us to establish 1018 units of meaning. These units, when exhaustively considered, evidenced convergences that led to the constitution of five nuclei of ideas. Their analysis revealed, under a mode of manifestation implicit to the said by the teachers, that adopting modeling means inhabiting its place, which includes placing ones in a condition of closeness that allows us to feel it close to one another. This movement, which ultimately stems from the teacher's decision, is sometimes gradual and not conditioned to a specific periodicity of development of modeling activities. It involves seeking for proper ways of doing and being with Modeling that, although they are particular to each teacher, are not lonely, since teachers are in the world with them-others.